Large animal models in gynecology: status and future perspectives - Zhao, Dan; Li, Xue; Zheng, Xu; Xie, Xiangrui; Zhao, Yanan; Liu, Yang (Frontiers in Veterinary Science, 2025)
The purpose of this review is to evaluate the effectiveness of large animal models in gynecology research and provide future perspectives. Gynecological diseases are diverse and pose a serious threat to women’s physical and mental health. In addition to the commonly used small animal models, large animal models have gradually entered the field of gynecological research. Results suggest that large animal models offer significant advantages in simulating human physiological processes, despite ethical and practical challenges. This paper reviews the application of large animal models in the study of gynecological diseases, provides a summary of the research characteristics of large animal models, analyses the advantages and challenges of these models in disease research, and compares the research differences between large and small animal models. It also discusses the relationship between these models and new alternative models, with a view to providing more new ideas for the selection of animal models in the study of gynecological diseases.